2016
DOI: 10.4992/jjpsy.87.15316
|View full text |Cite
|
Sign up to set email alerts
|

Do envious people show better performance?: Focusing on the function of benign envy as personality trait

Abstract: This study focused on the differences between two, subtypes of envy known as "benign envy" and "malicious envy" as personality traits, and examined the effects of these traits on academic achievement. Two hundred fifty-one university students participated in the study. Both benign envy and malicious envy were found to be independent as also found in a previous study by Lange & Crusius (2015), and a high criterion-related validity was revealed by an association with characteristic variables such as dispositiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
1
13
0
3
Order By: Relevance
“…The students with higher levels of benign envy were found to set goals higher and as a result, achieved higher levels of academic performance. In contrast, no such effect was found for malicious envy [12].…”
Section: Envied: the Targeted Person/group Of Persons Who Is/are Envimentioning
confidence: 50%
“…The students with higher levels of benign envy were found to set goals higher and as a result, achieved higher levels of academic performance. In contrast, no such effect was found for malicious envy [12].…”
Section: Envied: the Targeted Person/group Of Persons Who Is/are Envimentioning
confidence: 50%
“…We add that these two constructs are separable in part because they produce different motivational states, which in turn result in different behavioral outcomes. Evidence for considering benign and malicious envy to be separate constructs has been further corroborated by research showing that students who exhibit high levels of benign envy as a personality trait had a propensity to set higher goals for themselves, and thus tended to perform better academically relative to their counterparts who had higher levels of malicious envy (Sawada & Fujii, 2016). We found that gratitude was negatively correlated with malicious envy, but showed no such relationship with benign envy.…”
Section: Discussionmentioning
confidence: 96%
“…Research on dispositional inclinations to experience envy (Çırpan & Özdoğru, 2017;Kwiatkowska, Rogoza, & Volkodav, 2018;Lange & Crusius, 2015a;Sawada & Fujii, 2016;Sterling et al, 2017) found two-factor solutions supporting a dual conceptualization.…”
Section: The Dual Approachmentioning
confidence: 99%